EFEK MEDIASI KEJELASAN PERAN, KEADILAN PROSEDURAL DAN MOTIVASI PADA PENGARUH PENGUKURAN KINERJA NONFINANSIAL TERHADAP KINERJA MANAJERIAL - Anggriawan, Muhammad Angga (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
This study aims to examine the effect of nonfinancial performance measurement, role clarity, procedural fairness, and motivation to managerial performance. The object of this research is a manufacturing company in Banten Province. This research is empirical research with purposive sampling technique in data collection. Data obtained by answer questionnaire that has been disseminated to Production Manager, Sales Manager, Marketing Manager at manufacturing company in Banten Province, with return of questionnaire reached 89% that is 67 respondent, but questionnaire that can be tested only 77% that is 58 responden karna questionaire returned as many as 12% ie 9 respondents are not filled by respondents (empty). Data analysis was done with Structural Equation Model (SEM) with Smart PLS program (Partial Least Square). The results showed that clarity of roles, procedural keadilan, and motivation significantly influence the managerial performance but nonfinancial performance measurement does not significantly affect managerial performance. Curiously, role clarity, procedural fairness, and motivation have a mediating effect between nonfinancial performance measurements on managerial performance.Keyword : Measurement of Nonfinancial Performance, Roles Clarity, Procedural Fairness, Motivation, Managerial Performance